A Metal‐Free Direct Arene C−H Amination. Issue 11 (1st April 2021) - Wang, Tao; Hoffmann, Marvin; Dreuw, Andreas; Hasagić, Edina; Hu, Chao; Stein, Philipp M.; Witzel, Sina; Shi, Hongwei; Yang, Yangyang; Rudolph, Matthias; Stuck, Fabian; Rominger, Frank; et al.
Abstract: The synthesis of aryl amines via the formation of a C−N bond is an essential tool for the preparation of functional materials, active pharmaceutical ingredients and bioactive products. Usually, this chemical connection is only possible by transition metal‐catalyzed reactions, photochemistry or electrochemistry. Here, we report a metal‐free arene C−H amination using hydroxylamine derivatives under benign conditions. A charge transfer interaction between the aminating reagents TsONHR and the arene substrates enables the chemoselective amination of the arene, even in the presence of various functional groups. Oxygen was crucial for an effective conversion and its accelerating role for the electron transfer step was proven experimentally. In addition, this was rationalized by a theoretical study which indicated the involvement of a dioxygen‐bridged complex with a "Sandwich‐like" arrangement of the aromatic starting materials and the aminating agents at the dioxygen molecule. Abstract :